Interactive methods in teaching English in higher education - Parpiyeva , Umida (The Lingua Spectrum, 2025)
This study explores the effectiveness of interactive methods in teaching English in higher education, emphasizing the need for advanced approaches to develop students’ knowledge and skills. It highlights the growing demand for mastering English, particularly in fields where global communication and collaboration are essential.The research examines the distinctive features of interactive methods, their application in classroom settings, and their role in the educational process. Strategies aimed at actively engaging students in the learning process and improving their communication skills are developed. Additionally, the importance of group work, role-playing, debates, and other interactive exercises in making English learning an engaging and motivating experience is emphasized.The methodological foundations presented in the study are noted for their potential to enhance the effectiveness of education through the application of innovative technologies in modern teaching processes. The theoretical and practical significance of the findings is discussed, showing how the results can serve as an important resource for overcoming challenges in teaching English. By implementing these approaches, the study aims to improve the quality of English language teaching in higher education institutions, prepare students for the dynamic demands of the modern labor market, and enhance their communication competencies.